NAMPT-targeting PROTAC promotes antitumor immunity via suppressing myeloid-derived suppressor cell expansion - Ying Wu; Congying Pu; Yixian Fu; Guoqiang Dong; Min Huang; Chunquan Sheng (Elsevier, 2022)
Nicotinamide phosphoribosyl transferase (NAMPT) is considered as a promising target for cancer therapy given its critical engagement in cancer metabolism and inflammation. However, therapeutic benefit of NAMPT enzymatic inhibitors appears very limited, likely due to the failure to intervene non-enzymatic functions of NAMPT. Herein, we show that NAMPT dampens antitumor immunity by promoting the expansion of tumor infiltrating myeloid derived suppressive cells (MDSCs) via a mechanism independent of its enzymatic activity. Using proteolysis-targeting chimera (PROTAC) technology, PROTAC A7 is identified as a potent and selective degrader of NAMPT, which degrades intracellular NAMPT (iNAMPT) via the ubiquitin-proteasome system, and in turn decreases the secretion of extracellular NAMPT (eNAMPT), the major player of the non-enzymatic activity of NAMPT. In vivo, PROTAC A7 efficiently degrades NAMPT, inhibits tumor infiltrating MDSCs, and boosts antitumor efficacy. Of note, the anticancer activity of PROTAC A7 is superior to NAMPT enzymatic inhibitors that fail to achieve the same impact on MDSCs. Together, our findings uncover the new role of enzymatically-independent function of NAMPT in remodeling the immunosuppressive tumor microenvironment, and reports the first NAMPT PROTAC A7 that is able to block the pro-tumor function of both iNAMPT and eNAMPT, pointing out a new direction for the development of NAMPT-targeted therapies.